2005
DOI: 10.1001/archotol.131.8.675
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Dizziness and Anxiety

Abstract: To investigate the hypothesis that the efficacy of selective serotonin reuptake inhibitors (SSRIs) for chronic subjective dizziness (CSD) and anxiety depends on the longitudinal pattern of the patients' symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 20 publications
(24 reference statements)
0
23
0
4
Order By: Relevance
“…For example, previous studies indicate that SSRIs have parallel effects on dizziness symptoms and anxiety in patients with high Subjective Depression Scale scores and clinical evidence of organic vestibular disease [132], and patients with chronic subjective dizziness [4,128]. It is noteworthy that the three symptom scales showing improvement in the former study [132] include the main components of SMD.…”
Section: Diagnostic and Neurotherapeutic Implicationsmentioning
confidence: 87%
“…For example, previous studies indicate that SSRIs have parallel effects on dizziness symptoms and anxiety in patients with high Subjective Depression Scale scores and clinical evidence of organic vestibular disease [132], and patients with chronic subjective dizziness [4,128]. It is noteworthy that the three symptom scales showing improvement in the former study [132] include the main components of SMD.…”
Section: Diagnostic and Neurotherapeutic Implicationsmentioning
confidence: 87%
“…VID is a chronic disorder, often triggered by an acute vestibular disorder, during which these visual stimuli trigger or aggravate vestibular symptoms (Guerraz et al, 2001, Pavlou et al, 2006). Chronic vestibular symptoms triggered by an acute vestibular disorder can also manifest as chronic subjective dizziness (CSD) (Staab et al, 2004, Staab and Ruckenstein, 2005) or phobic postural vertigo (PPV) (Brandt, 1996, Kapfhammer et al, 1997), of which the former is also characterized by increased sensitivity to visual motion (Staab and Ruckenstein, 2005). When a group of 21 patients with VID were assessed for changes in postural sway and SVV in the presence of a tilted visual frame or a rotating visual disc, they displayed increased sway and poorer accuracy in estimating the gravitational vertical compared to controls - suggesting an influence of (moving) visual surroundings on vestibular processing (Guerraz et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A separate study using fMRI with vestibular stimulation reported localized hypofunction and decreased connectivity between several brain regions including the superior temporal gyrus, anterior insula/inferior frontal gyrus, middle occipital gyrus and hippocampus in patients with chronic subjective dizziness (CSD) compared to controls (Indovina et al, 2015). The authors suggested that the VID symptoms, often present in CSD patients (Staab and Ruckenstein, 2005), might be related to the decreased connectivity between anterior insula and middle occipital gyrus together with the decreased activity in anterior insula, anterior cingulate cortex and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that these medications are effective in managing CSD. [23][24][25] Approximately 50% of patients given an SSRI had complete remission of symptoms, and 70% demonstrated a positive effect. [23][24][25] Physicians should recognize and counsel patients that with CSD.…”
Section: Report Of Casementioning
confidence: 99%
“…[23][24][25] Approximately 50% of patients given an SSRI had complete remission of symptoms, and 70% demonstrated a positive effect. [23][24][25] Physicians should recognize and counsel patients that with CSD. 10,26,27 Osteopathic Considerations A whole-person approach is emphasized in osteopathic philosophies, through which the union of body, mind, and spirit is recognized.…”
Section: Report Of Casementioning
confidence: 99%